Grammatical Features of African American Vernacular English In King of Killbranch Album - Rio Raka Fatra; Anit Pranita Devi (Modality Journal: International Journal of Linguistics and Literature, 2024)
This research aimed to identify and analyze the grammatical features of African American Vernacular English (AAVE) used in King Of Killbranch album by BIG30. This research also aimed to identify the most dominant grammatical feature of African American Vernacular English (AAVE) used in King Of Killbranch album. A case study method was applied to this research. The grammatical features of AAVE were analyzed based on the theories proposed by Wolfram (2004). The data analysis procedures included reading the song lyrics, sorting and identifying song lyrics that contain AAVE grammatical features, and examining the data using Wolfram's theory. The results showed that 10 grammatical features were found such as copula absence, invariant "be", completive done, sequential be done, remote “been”, simple past had+verb, specialized auxiliaries, irregular verbs, subject-verb agreement, other verb phrase structures, negation, nominals, and question formation. Furthermore, the most dominant grammatical feature of AAVE in this album is copula absence. Abstrak   Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis fitur gramatikal African American Vernacular English (AAVE) yang digunakan dalam album King Of Killbranch milik BIG30. Penelitian ini juga bertujuan untuk mengidentifikasi fitur gramatikal African American Vernacular English (AAVE) yang paling dominan digunakan dalam album King Of Killbranch. Metode studi kasus diterapkan pada penelitian ini. Fitur tata bahasa AAVE dianalisis berdasarkan teori yang diajukan oleh Wolfram (2004). Prosedur analisis data meliputi membaca lirik lagu, mengidentifikasi dan mengklasifikasikan lirik lagu yang mengandung ciri gramatikal AAVE, dan menguji data menggunakan teori Wolfram. Hasil penelitian menunjukkan bahwa ditemukan 10 ciri gramatikal seperti copula absence, invariant "be", completive done, sequential be done, remote “been”, simple past had+verb, specialized auxiliaries, irregular verbs, subject-verb agreement, other verb phrase structures, negation, nominals, dan question formation Selain itu, ciri gramatikal AAVE yang paling dominan dalam album ini adalah copula absence.